Ensuring the enterprise functioning under conditions of uncertainty: parametric assessment - Vynogradova, Оlena; Lehominova, Svitlana; Kapeliushna, Tetiana; Goloborodko, Alona (Technology audit and production reserves, 2025)
The study substantiates the importance of enterprise awareness of its environment for making managerial decisions under conditions of uncertainty. The object of the study is information and its asymmetry in the enterprise awareness of its environment when making decisions under conditions of uncertainty. Making management decisions in conditions of uncertainty requires a high-quality information base, which necessitates the need to improve approaches to assessing the impact of challenges on the enterprise functioning. The SPOD (Strengths, Problems, Opportunities, Definite) matrix is used to analyze enterprise challenges. It is emphasized that the classical SPOD matrix has a static nature and does not account for informational influences; therefore, it is proposed to extend it with a component U (Uncertainty) to reflect the dynamics of uncertainty. The entropic nature of economic processes is identified, revealing that increasing entropy reduces the resilience of economic systems and necessitates adaptive management. The proposed approach, based on the entropic measurement of uncertainty, enables a quantitative assessment of the degree of unpredictability of challenges. The variability of the enterprise environment under uncertainty imposes certain limitations on the applicability of the research results, particularly those related to the integration of non-formalized factors – socio-psychological, reputational, communicative – which are difficult to represent quantitatively. Ensuring the relevance of data is required to prevent overloading the matrix with excessive variables. The combining the SPOD/U method with an entropic assessment establishes a methodological foundation for evaluating environmental uncertainty of enterprise functioning. The research findings are particularly relevant for enterprises operating in the field of electronic communications.